The impact of trade barrier, market demand, and consumer behaviour on business performance of Small and Medium Enterprise (SME’s) during the COVID-19 pandemic - Johari, Jalila; Abu Bakar, Umi Najihah (University Teknologi Mara, 2022)
The purpose of this study is to investigate the impact of government trade barriers, consumer behaviours, and market demand on the business performance of small and medium-sized enterprises in Malaysia during the COVID-19 pandemic. The pandemic outbreak and subsequent lockdowns took a heavy toll on SME’s, affecting the economy, society, health, and the life cycle. SMEs have faced problems such as a labour shortage, a drop in demand, a shortage of raw materials, changes in consumer behaviour, and trade barriers imposed by governments through the movement control order (MCO). The data is gathered through the distribution of questionnaires, and the sample size is 107 respondents in the most affected states by the COVID19 pandemic. This study employs a quantitative approach, and it is analysed using regression. According to the findings of this study, changes in market demand have had a significant impact on the business performance of SMEs. It demonstrates that a drop in customer demand has resulted in a decrease in profit. The implications of this research are to encourage business actors to shift their market focus to satisfy demand and requirement changes, as well as to urge more severe measures to improve the performance of SME’s.